Axial Spondyloarthritis: Patient-Reported Impact in Europe - Garrido-Cumbrera, Marco (Springer Nature, 2022)
This open access book provides an overview of the International Map of Axial Spondyloarthritis (IMAS) project -focusing on Europe-, a wide-ranging, multi-disciplinary collaboration between academic groups, Health Care Professionals (HCPs), patient organizations and Novartis. IMAS was conceived to improve knowledge of Axial Spondyloarthritis (axSpA) and raise awareness of its heavy burden globally. By asking more than 2,000 patients across Europe about the impact of axSpA on multiple aspects of their life, the full extent of this disease was investigated from a direct patient perspective. This allowed a unique understanding of how living with axSpA affects the daily lives and well-being of patients, and how this varies between European countries. Axial Spondyloarthritis: Patient-Reported Impact in Europe highlights opportunities for progressing quality patient care to be applied to health services globally. HCPs, policy makers and patients will find this book to be an indispensable resource for improving the understanding of this chronic condition, including patients' clinical outcomes, the protection of those at risk of psychological distress, and the economic burden on patients and society.